2016
DOI: 10.1556/1886.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation of Shigella spp. from enteroinvasive E. coli

Abstract: A real-time polymerase chain reaction (PCR) assay, amplifying the genes encoding lactose permease (lacY) and invasion plasmid antigen H (ipaH), was run on 121 isolates phenotypically classified as Shigella spp., enteroinvasive Escherichia coli (EIEC), or EIEC O nontypable (ONT). The results were compared with data from a generic E. coli multiple-locus variable-number of tandem repeat analysis (MLVA) and a Shigella MLVA.The real-time PCR verified all Shigella spp. (n = 53) as Shigella (lacY negative) and all EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…lacY (a lactose permease gene). Two previous studies 43,44 found that 100% of their Shigella stool sample isolates were ipaH positive/ lacY negative, whereas their EIEC isolates were more likely to be ipaH positive/ lacY positive.…”
Section: Discussionmentioning
confidence: 98%
“…lacY (a lactose permease gene). Two previous studies 43,44 found that 100% of their Shigella stool sample isolates were ipaH positive/ lacY negative, whereas their EIEC isolates were more likely to be ipaH positive/ lacY positive.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Lobersli et al. [11] established a duplex real-time PCR ( ipa H and lac Y) to differentiate EIEC and Shigella spp., where lac Y is specific to E. coli. This PCR target differentiated Shigella spp.…”
Section: Currently Used Molecular Methods For Differentiation Of mentioning
confidence: 99%
“…(ii) lacY. EclacY was reported to be absent from Shigella organisms except S. sonnei and S. dysenteriae 1 while present in most EIEC isolates (64). A remnant from the 5= end of EclacY was detected in 21 of 22 S. sonnei (107 to 270 bp) and 8 of 8 S. dysenteriae 1 (361 to 475 bp) genomes, respectively.…”
Section: Resultsmentioning
confidence: 98%